2013
DOI: 10.1152/japplphysiol.01389.2012
|View full text |Cite
|
Sign up to set email alerts
|

Responses of vestibular nucleus neurons to inputs from the hindlimb are enhanced following a bilateral labyrinthectomy

Abstract: Vestibular nucleus neurons have been shown to respond to stimulation of afferents innervating the limbs. However, a limitation in the potential translation of these findings is that they were obtained from decerebrate or anesthetized animals. The goal of the present study was to determine whether stimulation of hindlimb nerves similarly affects vestibular nucleus neuronal activity in conscious cats, and whether the responsiveness of neurons to the stimuli is altered following a bilateral labyrinthectomy. In la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Similarly, another study indicated that the responses to vestibular stimulation of neurons in the rostral ventrolateral medulla that participate in cardiovascular regulation are exaggerated in decerebrate cats (Destefino et al 2011). Other studies compared responses to whole-body rotations of neurons in the caudal vestibular nuclei in decerebrate (Endo et al 1995; Arshian et al 2013) and conscious felines (Miller et al 2008a; McCall et al 2013) and reported little difference in findings between the preparations. Hence, it appears that decerebration is more likely to unmask responses to vestibular stimulation in brain regions that receive multisynaptic inputs from the labyrinth than areas that receive inputs directly from the inner ear.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study indicated that the responses to vestibular stimulation of neurons in the rostral ventrolateral medulla that participate in cardiovascular regulation are exaggerated in decerebrate cats (Destefino et al 2011). Other studies compared responses to whole-body rotations of neurons in the caudal vestibular nuclei in decerebrate (Endo et al 1995; Arshian et al 2013) and conscious felines (Miller et al 2008a; McCall et al 2013) and reported little difference in findings between the preparations. Hence, it appears that decerebration is more likely to unmask responses to vestibular stimulation in brain regions that receive multisynaptic inputs from the labyrinth than areas that receive inputs directly from the inner ear.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons in decerebrate and conscious cats of the effects of electrical stimulation of hindlimb nerves on vestibular nucleus neuronal activity revealed some similarities, as well as differences (238, 239). Similarities across preparations include the following: the majority of vestibular nucleus neurons received convergent limb inputs from multiple nerves; response latencies were ~20 ms suggesting that polysynaptic pathways conveyed limb inputs to vestibular nucleus neurons; most responses were excitatory; and the proportion of neurons activated by hindlimb nerve stimulation increased after bilateral labyrinthectomy (238, 239). By contrast, low-intensity stimuli [<twice threshold (T) for eliciting a compound action potential in the stimulated nerve] elicited changes in activity of many vestibular nucleus neurons in decerebrate animals, but such low-intensity stimuli were ineffective in conscious animals.…”
Section: Transformation Of Vestibular Reflexes By Descending Pathwaysmentioning
confidence: 98%
“…The effects of hindlimb somatosensory inputs on the activity of vestibular nucleus neurons have been studied in both decerebrate and conscious cats by the same investigators, using the same equipment and methodology during experiments in both preparations, thus permitting comparisons (75, 78, 238, 239). Comparisons in decerebrate and conscious cats of the effects of electrical stimulation of hindlimb nerves on vestibular nucleus neuronal activity revealed some similarities, as well as differences (238, 239).…”
Section: Transformation Of Vestibular Reflexes By Descending Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Several physiologic studies provide evidence supporting this hypothesis. VN neurons respond to electrical stimulation of hindlimb nerves (Wilson et al 1966; Jian et al 2002; McCall et al 2013) and the activity of VN neurons in decerebrate felines is modulated during hindlimb movement (Fredrickson et al 1966; Orlovsky 1972; Arshian et al 2014), with most VN neurons encoding the direction of hindlimb movement (Arshian et al 2014). …”
Section: Introductionmentioning
confidence: 99%